The role of communication skills in the effectiveness of work teams a case study of a salt refining complex in El Outaya - Biskra Province - zaoui, abdesselam; ichouch, mohamed El.hafedh (Journal of Social Sciences and Humanities, 2024)
This study aims to identify the nature of the influence relationship between communication skills and work teams at the level of employees of the salt refining complex in El Wattaya, in the Wilayat of Biskra, where we distributed 80 questionnaires and the number of questionnaires valid for analysis was 57. The study reached results according to which oral communication skills (listening skills and event skills) and written communication skills (reading skills and writing skills) have a statistically significant impact relationship on the dependent variable work teams.